Socio-demographic determinants of pregnancy induced hypertension - Naseer, Syed; Wani, Manzoor Ahmed; Altaf, Tayiba; Uzma, Syed; Mubashir, Syed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Pregnancy induced hypertension is a major health problem affecting the maternal and neonatal health, this serious obstetric problem occurs in women with pre-existing primary or secondary hypertension or women who are not having hypertension before pregnancy. Methods: A cross-sectional study was carried out among the women suffering from pregnancy induced hypertension, admitted in the gynaecology wards of Lal-Ded hospital, Srinagar from May 2021 to July 2021. A total of 100 sample patients were taken and data was collected using structured questionnaire. Data was analyzed by using SPSS 16.0. Results: Women suffering from PIH were having the mean age of 28 years with the mean gestation period being 36 weeks+6 days. Their mean systolic blood pressure was 150 mmHg and mean diastolic blood pressure was 98 mmHg. Out of 100 women, 75% were multigravida and 25% were primigravida and 40% were having a history of hypertension before pregnancy. Only 48% had a history of PIH in previous pregnancies while 52% had no such history. In 14% of PIH patients, there was an associated systemic disease. Out of 100, 48% belonged to rural areas, 15% were living in urban areas while 37% resided in semi-urban district. 46% of the patients were illiterate while 54% were educated, be it primary, secondary or higher level. Only 8% were employed while the rest were house wives. 11% had not been to a gynaecologist during their pregnancy while 13% had one visit done, 30% two and 46% had three or more antenatal visits. 67% had a history of hypertension among blood relatives. Conclusions: Pregnancy induced hypertension and socio-demographic determinants like the age of mother, blood pressure, history of hypertensive disorders in blood relatives,do show correlation Among these, history of PIH and chronic hypertensive disorders in blood relatives and high BP seemed to be the strongest risk factors among these 100 women.